Kinetic analysis of non-isothermal calorimetric data - Málek, Jiří (Univerzita Pardubice, 1996)
A simple and reliable method of kinetic analysis of non-isothermal calorimetric data has been developed. This method allows to find appropriate model characterizing the kinetics of the process studied as well as to calculate reliable kinetic parameters. The application of this method is demonstrated for three different processes: (i) Curing reaction of an epoxy resin (ii) Crystallization kinetics of a chalcogenide glass (iii) Crystallization kinetics of zirconia gel The reliability of calculated kinetic parameters is tested by comparing calculated and experimental isothermal kinetic data. It is shown that a very good prediction of isothermal behavior can be obtained. Such modelling can be very useful for preparation of materials with defined properties.